ANALISIS STRATEGI PEMBERANTASAN KORUPSI DI INDONESIA DALAM PERSFEKTIF HUKUM ADMINISTRASI NEGARA - Ratna Dewi, Nabilah (JOURNAL IURIS SCIENTIA, 2023)
In Indonesia, corruption has become an open secret and has broad implications in people's lives. Corruption is one form of abuse of authority so that it intersects with administrative law which has an important role to supervise the government. This paper aims to analyze strategies to eradicate corrupt practices in Indonesia based on state administrative law. The research method used in this paper is juridical normative. Based on the results of the discussion, it can be concluded that the functions and roles of the State Administration Law in eradicating corruption in Indonesia, including: (1) Legal supervision of government administration and (2) Bureaucratic reform. Strengthening the State Administration Law is important as one of the effective options as a form of prevention and eradication of corrupt practices in Indonesia. There are several strategies to eradicate corrupt practices in Indonesia based on the State Administration Law, including: (1) Forming a leadership spirit for good governance, (2) Improving government administration institutions, (3) Strengthening the law, (4) Improving the integrity and ethics of state administration, and (5) Establishment and strengthening of Anti-Corruption Institutions. Abstrak Di Indonesia korupsi sudah menjadi rahasia umum dan berimplikasi luas dalam kehidupan masyarakat. Korupsi merupakan salah satu bentuk penyalahgunaan wewenang sehingga bersinggungan dengan hukum administrasi yang memiliki peran penting untuk mengawasi pemerintahan. Tulisan ini bertujuan untuk menganalisis strategi pemberantasan praktik korupsi di Indonesia berlandaskan hukum administrasi negara. Metode penelitian yang digunakan dalam tulisan ini adalah yuridis normative. Berdasarkan hasil pembahasan, dapat disimpulkan bahwa fungsi dan peran Hukum Administrasi Negara dalam pemberantasan korupsi di Indonesia, diantaranya adalah: (1) Pengwasan hukum penyelenggaraan pemerintahan dan (2) Reformasi birokrasi. Penguatan Hukum Administrasi Negara penting sebagai salah satu opsi yang efektif sebagai bentuk upaya pencegahan dan pemberantasan praktik korupsi di Indonesia. Terdapat beberapa strategi pemberantasan praktik korupsi di Indonesia berlandaskan Hukum Administrasi Negara, diantaranya adalah: (1) Membentuk jiwa kepemimpinan atas pemerintahan yang baik, (2) Perbaikan lembaga penyelenggara pemerintahan, (3) Penguatan hukum, (4) Meningkatkan integritas dan etika penyelenggaraan negara, dan (5) Pembentukan dan penguatan Lembaga Anti Korupsi.